2022
DOI: 10.1186/s12885-022-09556-7
|View full text |Cite
|
Sign up to set email alerts
|

T-DM1 efficacy in trastuzumab-pertuzumab pre-treated HER2 positive metastatic breast cancer patients: a meta-analysis

Abstract: Background Current guidelines consider T-DM1 the standard 2nd line therapy for HER2 positive metastatic breast cancer (MBC) patients following trastuzumab (T) + pertuzumab (P) and taxane 1st line treatment. Despite this, there are no prospective studies supporting this sequence. Methods We performed a meta-analysis using real world data to determine the efficacy of T-DM1 after 1st line TP in HER2 positive MBC patients. We used a random-effect model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“… 24 28 A metanalysis to determine the efficacy of T-DM1 after first-line trastuzumab and pertuzumab use in HER2-positive breast cancer reported that the efficacy of T-DM1 after pertuzumab use was similar to that of the EMILIA study in the third line or more lines, but not in the second line. 29 Sanglier et al reported that pertuzumab-treated patients entering the T-DM1 cohort earliest had more aggressive disease and poorer outcomes than patients entering the study in the most recent years and described this result as a selection bias. 30 The control group in DESTINY-Breast03, with 75% of patients receiving a prior second or later line, was similar to that of our study, with approximately 65% of patients receiving a prior second or later line.…”
Section: Discussionmentioning
confidence: 99%
“… 24 28 A metanalysis to determine the efficacy of T-DM1 after first-line trastuzumab and pertuzumab use in HER2-positive breast cancer reported that the efficacy of T-DM1 after pertuzumab use was similar to that of the EMILIA study in the third line or more lines, but not in the second line. 29 Sanglier et al reported that pertuzumab-treated patients entering the T-DM1 cohort earliest had more aggressive disease and poorer outcomes than patients entering the study in the most recent years and described this result as a selection bias. 30 The control group in DESTINY-Breast03, with 75% of patients receiving a prior second or later line, was similar to that of our study, with approximately 65% of patients receiving a prior second or later line.…”
Section: Discussionmentioning
confidence: 99%
“…Seven RCTs of 3870 patients tested three types of ADCs (T-DM1, SYD985, and T-Dxd). Notably, the global multicenter phase III clinical trials DESTINY BREAST 02 and TULIP (reported in 2023 and 2021, respectively) were not included in previous meta-analyses [ 39 41 ]. Comparatively, the present meta-analysis included high-quality trials with relatively larger cohorts and more available drugs, thus offering more reliable conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Building on previous experience with trastuzumab, whereby it has been shown that maintenance of HER2 blockade beyond progression in the second- and third-line settings provides clinical benefit and prolongs survival, it is advisable to maintain HER2 blockade also upon T-DXd failure. 53 , 54 , 55 , 56 In this context, preferred chemotherapeutic regimens with recognized activity in HER2-positive BC are represented by anthracyclines, eribulin, and vinorelbine. 7 In addition, given the lack of data regarding common resistance mechanisms, it might be also advisable to carry out tumor re-biopsy upon T-DXd failure in order to better guide treatment decision making, as well as optimally refer patients to clinical trials, upon availability and feasibility.…”
Section: What To Do After Progression On Trastuzumab Deruxtecan?mentioning
confidence: 99%
“…Lastly, real-world data concerning the activity of the aforementioned regimens upon T-DXd failure could further aid in the identification of most active compounds, as in the previous case of T-DM1 in pertuzumab pre-treated patients. 56 …”
Section: What To Do After Progression On Trastuzumab Deruxtecan?mentioning
confidence: 99%